Mercury in a stream-lake network of Andean Patagonia (Southern Volcanic Zone): Partitioning and interaction with dissolved organic matter. (April 2018) - Soto Cárdenas, Carolina; Diéguez, María del Carmen; Queimaliños, Claudia; Rizzo, Andrea; Fajon, Vesna; Kotnik, Jože; Horvat, Milena; Ribeiro Guevara, Sergio
Abstract: Lake Nahuel Huapi (NH) is a large, ultraoligotrophic deep system located in Nahuel Huapi National Park (NHNP) and collecting a major headwater network of Northwestern Patagonia (Argentina). Brazo Rincón (BR), the westernmost branch of NH, is close to the active volcanic formation Puyehue-Cordón Caulle. In BR, aquatic biota and sediments display high levels of total Hg (THg), ranging in contamination levels although it is an unpolluted region. In this survey, Hg species and fractionation were assessed in association with dissolved organic matter (DOM) in several aquatic systems draining to BR. THg varied between 16.8 and 363 ng L −1, with inorganic Hg (Hg 2+ ) contributing up to 99.8% and methyl mercury (MeHg) up to 2.10%. DOC levels were low (0.31–1.02 mg L −1 ) resulting in high THg:DOC and reflecting in high Hg 2+ availability for binding particles (partitioning coefficient log Kd up to 6.03). In streams, Hg fractionation and speciation related directly with DOM terrestrial prints, indicating coupled Hg-DOM inputs from the catchment. In the lake, DOM quality and photochemical and biological processing drive Hg fractionation, speciation and vertical levels. Dissolved gaseous Hg (Hg 0 ) reached higher values in BR (up to 3.8%), particularly in upper lake layers where solar radiation enhances the photoreduction of Hg 2+ and Hg-DOM complexes. The environmental conditions in BR catchment promote Hg 2+ binding to abiotic particles and bioaccumulation and the production of Hg 0, features enhancing Hg mobilization among ecosystem compartments. Overall, the aquatic network studied can be considered a "natural Hg hotspot" within NHNP. Graphical abstract: Image 1 Highlights: High THg levels were found in a stream-lake network placed within a volcanic area. High THg:DOC ratios determined high Hg 2+ binding to abiotic and biotic particles. Stream Hg species are related to terrestrial DOM, reflecting inputs from the catchment. Lake Hg speciation related to DOM quality and photochemical and biological processes. Hg 0 was higher in the upper lake layers due to photo- and biological reduction.